Improvement in Contact Strength of Si3N4/SiC Composite by Crack Healing. (11th June 2013) - Takahashi, Koji; Takahashi, Keita; Ando, Kotoji
Abstract : Ceramics have been used as bearing and cutting tool components, which are subjected to contact loading during their operation. The presence of surface cracks on these components decreases their contact strength. Thus, the reliability of ceramic components can be increased by improving their contact strength through crack healing. In the present study, the effects of crack healing on the contact strength of a silicon carbide-(SiC-) reinforced silicon nitride (Si3 N4 ) composite subjected to various machining processes were investigated. The contact strength of this composite was evaluated using a sphere indentation test in which acoustic emission was used. The results showed that the contact strength of the composite improved when it was subjected to crack healing in combination with rapping; this was true even when the composite had cracks due to a heavy machining process.